Does Islamic Work Ethic Influence Employees Innovation Capability? - Nadia Adriane Ricadonna (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2021)
Innovation Capability is one of the phenomena faced by Sharia Rural Banks in Indonesia. In the era of revolution 4.0, currently the role of human resource cannot be replaced by technological sophistication. The problem that exists in Sharia Rural Banks is not yet available human resources capable of creating innovation products and services that can meet the needs of its customers. So this research is focused on being able to test and analyze the effect of Islamic Work Ethics, Knowledge Sharing and Empowerment on Innovation Capabilites.This research is a quantitative study using primary data. The sample in this study were 100 respondents of People’s Financing Bank Employees in the city of Semarang. The data collected is tested and analyzed using the SMART PLS program by testing the outer model and inner model. The results of the SMART PLS test show that Islamic Work Ethics, Knowledge Sharing and Empowerment also have a positive and significant effect on the Innovation Capabilities.